The use of audio-visual media in improving culinary students learning outcomes in chicken carcass material - Mashudi Mashudi; Kokom Komariah; Moh. Farizqo Irvan (Jurnal Pendidikan Vokasi, 2021)
This research aimed to find out the effectiveness of audio-visual media (picture, video, audio) on culinary students' learning outcomes in chicken carcass material. The researcher implemented a quasi-experimental method with a nonequivalent control group design. The subjects of this study were the 10th-grade students of SMK Negeri 8 Medan, Academic Year 2016/2017. Cluster random sampling was applied in this study, which consisted of one experimental class and one control class. Meanwhile, some hypothetical tests used in this study were n-gain, independent t-test, and dependent t-test. The n-gain score of learning outcomes in the experimental class is higher than the control class, which is 0.5 and categorized as moderate. Furthermore, students' learning outcomes between those taught using audio-visual media and without audio-visual media in chicken carcass material indicated a significant difference with a significance score of 0.000 â‰¤ 0.05. Thus, the audiovisual media effectively improves the learning outcomes of the 10th-grade students of the culinary department in Chicken Carcass material.